Nutritional Behaviours Of Adolescents Living In Rural Areas. Part 1. Characteristics Of Health Behaviours Regarding Regular Consumption Of Meals And Level Of Acceptance Of Own Body Weight - Cipora, Elżbieta; Smoleń, Ewa; Klimaszewska, Anna; Klimaszewska, Elżbieta; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Introduction. Proper nutrition consists in supplying the body with nutrients which are adequate from the aspect of their amount and quality, provide normal growth and maturation for an individual, as well as physical, mental, and emotional fitness. Eating habits are shaped as early as in childhood and constitute an important element of life style. It is very difficult to change bad dietary habits in children and adolescents, and these habits often continue into adulthood, and into own families. This is translated into the level of health in further periods of life in the form of serious consequences of chronic diseases, mainly on the metabolic background. Many studies confirmed that there occur clear differences in the observance of the principles of correct nutrition between adolescents living in large cities, and those from rural areas. Objective. The objective of the study was recognition and assessment of the types of nutritional behaviours among junior high school adolescents living in rural areas. Materials and Method.The study was conducted in June 2015, and covered a group of 115 adolescents attending a rural junior high school, randomly selected in the Sanok province. The method of a diagnostic survey and the Likert scale was applied. The research instrument was an author-constructed Questionnaire. Statistical analyses were performed using chi-square test and Cramer’s V test. The p values p<0.05 were considered statistically significant. Results. The majority of the examined school adolescents declared a normal body weight (80.9%). Boys reported correct nutrition more often than girls (67.6% vs. 30.8%). Slightly more than a half of the adolescents (52.2%) consumed breakfast every day. The largest number of the respondents (67.0%) admitted snacking between meals. Boys preferred grilled and fried meals (40.5%), whereas girls chose boiled food (66.7%); 42.6% of respondents indicated rational nutrition, and the same percentage tried to observe regular consumption of meals; only 30.4% of the total number of adolescents in the study consumed five meals daily. Conclusions. Despite the fact that more than a half of the respondents living in rural areas observe the principles of rational nutrition, this percentage is too low to state that their eating behaviours are correct. Rural children and adolescents require an early permanent health education in the area of nutrition and physical activity.